1997
DOI: 10.1093/carcin/18.9.1729
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of dietary chemoprotective agents in rat liver: induction of phase I and II drug metabolizing enzymes and aflatoxin B1 metabolism

Abstract: A range of potential chemoprotective agents, most of them natural dietary constituents, has been examined for ability to modulate both phase I (cytochrome P450 1A1, 1A2, 2B1/2, 2C11, 2E1, 3A, 4A) and phase II drug metabolizing enzymes (glutathione S-transferases, in particular subunits Yc2 and P, aflatoxin B1-aldehyde reductase and quinone reductase) in rat liver. In addition to assays of total enzyme activity and Western blots for individual isozymes, the ability of microsomes to metabolize aflatoxin B1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(100 citation statements)
references
References 5 publications
10
89
1
Order By: Relevance
“…Manson et a (1997) have shown that caffeic acid is a moderate inducer of phase II enzymes, but in our study caffeic acid did not increase DT-diaphorase activity.…”
Section: contrasting
confidence: 92%
See 1 more Smart Citation
“…Manson et a (1997) have shown that caffeic acid is a moderate inducer of phase II enzymes, but in our study caffeic acid did not increase DT-diaphorase activity.…”
Section: contrasting
confidence: 92%
“…Oltipraz, a D3T analogue, has been shown to induce phase II detoxifying enzymes and is currently undergoing clinical trials as a chemopreventive agent (Kensler and Helzlsouer, 1995). Isothiocyanates like sulforaphane, which is found in broccoli, can also induce phase II enzymes (Prestera et al, 1993;Manson et al, 1997), and have been shown to prevent the formation of carcinogen-induced tumours in animals (Zhang et al, 1994).…”
mentioning
confidence: 99%
“…Thus, phase I enzymes often result in bioactivation compared to inactivation resulting from phase II. According to Manson et al (1997) the result of exposure to an environmental toxin in terms of acute or chronic toxicity largely depends on the balance between these two processes. To better understand the antimutagenic mechanism of genistein on indirect mutagens, we focused on the metabolic activation of phase II enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Which pharmacologic properties of I3C could instead be implicated? Its ability to block tumor initiation has been rationalized in terms of upregulation of drug metabolizing enzymes, 27 whereas tumor suppression by I3C may be the consequence of modulation of pathways resulting in inhibition of cell proliferation or in compromised cell survival. 28,29 I3C has been shown to protect mice against hepatic damage induced by the hepatotoxicant carbon tetrachloride (CCl 4 ).…”
Section: Discussionmentioning
confidence: 99%